USING SOCIAL NETWORKS IN TEACHING ESP TO ENGINEERING STUDENTS - Nataliia Saienko; Oksana Semyda; Inna Akhmad (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
The present study examines students' and teachers' views on and attitudes to the use of different social networks in teaching English for specific purposes (ESP) to future engineers. It focuses on the types of work social networks can be used for, on language skills they help develop. The study was conducted with a survey method. The research was held at the National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute" and the sample was 170 full-time students of Energy Management and Energy Saving Institute and 60 lecturers of the Department of English for Engineering. It was conducted during December-February of 2019 - 2020 academic year. Within the context of the research, the students' and teachers' surveys were conducted. They were asked about their experience in using social networks and their application concerning university-related work and studies. The analysis of responses in the questionnaires showed that students and their teachers have a positive perception of using social media networks for English for specific purposes teaching in the classroom and outside. From the conducted research, we can conclude that using social networks is effective in ESP teaching and these advanced technologies can improve students' ESP proficiency, enhance their motivation for studying foreign languages, and can be used as corpora of authentic materials. The results of this research may be used for other studies concerning ESP teaching and technology application in this process.